Morphological abnormalities in some dominant fish species from the polluted site of the Pozim River (Udmurt Republic, Russia) - A.K. Mineev (Учёные записки Казанского университета: Серия Естественные науки)
Morphological abnormalities resulting from the anthropogenic load on juveniles of five cyprinid species (common roach (Rutilus rutilus Linnaeus, 1758), common rudd (Scardinius erythrophthalmus Linnaeus, 1758), ide (Leuciscus idus Linnaeus, 1758), European chub (Leuciscus cephalus Linnaeus, 1758), and common bream (Abramis brama Linnaeus, 1758)) that are dominant in the polluted site of the Pozim River near Izhevsk were analyzed based on the data obtained in 2012. The abundance of juveniles with abnormalities was high in all the fish species examined. The number of juveniles with morphological abnormalities decreased from the early larval to late fry stages, thereby confirming that the observed malformations are lethal to fish. None of the abnormalities was confined to a particular species, and this suggests that they are not species-specific.